Orientalist Typologies: The Cultural Politics of the Female Subject in Maxine Hong Kingston's The Woman Warrior and Joy Kogawa's Obasan - Hattori, Tomo (My University, 1994)
This thesis examines the persistence of psycholinguistic orientalist typologies in Maxine Hong Kingston's The Woman Warrior (1976), Joy Kogawa's Obasan (1981), and in selected criticism of the two works. The discussion of Orientalism uses Edward Said's Orientalism (1978) uses Edward Said's Orientalism (1978) as a point of reference but the specific operation of a psycholinguistic Orientalism is derived from the critique of Julia Kristeva's About Chinese Women (1977) by Gayatri Chakravorty Spivak, Rey Chow and Lisa Lowe. The Orientalist typology in The Woman Warrior and Obasan is organized around the mother-daughter relationships that are central in both works. The thesis reveals how these works have attracted a number of psychoanalytic readings that employ Kristeva's theory of poetic language but that are unaware of her Orientalist application of this theory in About Chinese Women. Orientalist typologies re-emerge in readings of The Woman Warrior and Obasan that use or allude to Kristeva's psycholinguistic theory but they are also embedded in the texts as well. Unlike the approach of earlier Asian American male critics such as Frank Chin, this thesis argues that the Orientalist aspects of The Woman Warrior and Obasan do not implicate the texts as necessarily flawed or incorrect. A generous understanding that texts by writers of East Asian ancestry can be Orientalist and that this operation can occur at the psychoanalytic level of the formation of the linguistic subject allows the writer's alienation from her culture of ancestry to function as an affirmative and crucial element in her story-making.
Keywords: English Language and Literature; English Language and Literature